Difference between revisions of "009A Sample Final A, Problem 6"
Jump to navigation
Jump to search
m |
m |
||
Line 29: | Line 29: | ||
|<br> <math>\frac{\sqrt{\frac{1}{x^{2}}}}{\,\,\,\frac{1}{x}}.</math> | |<br> <math>\frac{\sqrt{\frac{1}{x^{2}}}}{\,\,\,\frac{1}{x}}.</math> | ||
|- | |- | ||
− | |<br>This expression is equal to <math style="vertical-align: - | + | |<br>This expression is equal to <math style="vertical-align: -2%;">1</math> for positive values of <math style="vertical-align: 0%;">x</math>, and is equal to <math style="vertical-align: -3%;">-1</math> for negative values of <math style="vertical-align: 0%;">x</math>. Since multiplying <math style="vertical-align: -20%;">f(x)</math> by an expression equal to <math style="vertical-align: -2%;">1</math> doesn't change the limit, we will add a negative sign to our fraction when considering the limit as <math style="vertical-align: 0%;">x</math> goes to <math style="vertical-align: -2%;">-\infty</math>. Thus, |
|- | |- | ||
|<br> <math>\lim_{x\rightarrow\pm\infty}\frac{\sqrt{4x^{2}+3}}{10x-20}\,\,\cdot\,\,\pm\frac{\sqrt{\frac{1}{x^{2}}}}{\,\,\,\frac{1}{x}}=\lim_{x\rightarrow\pm\infty}\pm\frac{\sqrt{\frac{4x^{2}}{x^{2}}+\frac{3}{x^{2}}}}{\frac{10x}{x}-\frac{20}{x}} = \lim_{x\rightarrow\pm\infty}\pm\frac{\sqrt{4+\frac{3}{x^{2}}}}{10-\frac{20}{x}}=\pm\frac{2}{10}=\pm\frac{1}{5}</math> | |<br> <math>\lim_{x\rightarrow\pm\infty}\frac{\sqrt{4x^{2}+3}}{10x-20}\,\,\cdot\,\,\pm\frac{\sqrt{\frac{1}{x^{2}}}}{\,\,\,\frac{1}{x}}=\lim_{x\rightarrow\pm\infty}\pm\frac{\sqrt{\frac{4x^{2}}{x^{2}}+\frac{3}{x^{2}}}}{\frac{10x}{x}-\frac{20}{x}} = \lim_{x\rightarrow\pm\infty}\pm\frac{\sqrt{4+\frac{3}{x^{2}}}}{10-\frac{20}{x}}=\pm\frac{2}{10}=\pm\frac{1}{5}</math> | ||
|- | |- | ||
− | |<br>Thus, we have a horizontal asymptote at <math style="vertical-align: -23%;">y=-1/5</math> on the left (as <math style="vertical-align: 0%;">x</math> goes to <math style="vertical-align: - | + | |<br>Thus, we have a horizontal asymptote at <math style="vertical-align: -23%;">y=-1/5</math> on the left (as <math style="vertical-align: 0%;">x</math> goes to <math style="vertical-align: -2%;">-\infty</math>), and a horizontal asymptote at <math style="vertical-align: -23%;">y=1/5</math> on the right (as <math style="vertical-align: 0%;">x</math> goes to <math style="vertical-align: -3%;">+\infty</math>). |
|} | |} | ||
[[009A_Sample_Final_A|'''<u>Return to Sample Exam</u>''']] | [[009A_Sample_Final_A|'''<u>Return to Sample Exam</u>''']] |
Revision as of 19:33, 27 March 2015
6. Find the vertical and horizontal asymptotes of the function
Foundations: |
---|
Vertical asymptotes occur whenever the denominator of a rational function goes to zero, and it doesn't cancel from the numerator. |
On the other hand, horizontal asymptotes represent the limit as goes to either positive or negative infinity. |
Solution:
Vertical Asymptotes: |
---|
Setting the denominator to zero, we have |
which has a root at This is our vertical asymptote. |
Horizontal Asymptotes: |
---|
More work is required here. Since we need to find the limits at , we can multiply our by |
This expression is equal to for positive values of , and is equal to for negative values of . Since multiplying by an expression equal to doesn't change the limit, we will add a negative sign to our fraction when considering the limit as goes to . Thus, |
Thus, we have a horizontal asymptote at on the left (as goes to ), and a horizontal asymptote at on the right (as goes to ). |